PELATIHAN MENGOPTIMALKAN ARTIKEL ONLINE: TIPS & TRIK COPYWRITING UNTUK MAHASISWA JURNALISTIK - Simatupang, Yunita; Zanynu, M. Aswan; Dasmin, Dasmin; Wekogandhigrahita, Alfiansyah; Zainal Abidin H, La Ode Muhammad; Hasnani, Hasnani; Tunda, Amin (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2024)
More than half of Indonesia's population are internet users. Data from Internet World Stats in 2022 shows that the number of internet users in Indonesia has reached more than 76.5% of the total population. Internet users are not only young people but also the elderly. BPS data in 2020, out of 270.20 million people, 11.56% are Baby Boomers (55-70 years old). The elderly who are digital immigrants, namely those who were born when digital media did not exist, were then forced to move in droves to a completely digital world. Their habits and cultures are certainly very different. In this dilemma, it is not uncommon for elderly people to be the target of misuse of digital devices. Physical, structural and interpersonal factors make elderly people vulnerable to negative access in the digital world. The threat of digital fraud, hoaxes, and hate speech is also before them. So we need a digital literacy training program for the elderly, especially in accessing digital security.